ACTOR SEQUITUR FORUM REI: A THEORITICAL STUDY - Sujayadi, Sujayadi; Wijayanta, Tata; Herliana, Herliana (Faculty of Law Universitas Padjadjaran, 2023)
The actor sequitur forum rei principle is the primary basis for determining the relative competence of civil courts in countries that adopt civil law systems. In this article, the role of the actor sequitur forum rei will be examined theoretically by analyzing theories related to personal jurisdiction, categorization of jurisdiction, and procedural justice theory. The analysis results indicate that actor sequitur forum rei is founded on the theory of power and is classified as a